García Márquez's Literary Smuggling in The Story of a Shipwrecked Sailor. - Muñoz-Solano, Néfer (Texas Studies in Literature & Language)
The article focuses on Colombian novelist Gabriel García Márquez's unique blend of journalism and fiction in "The Story of a Shipwrecked Sailor," and it highlights the challenges to journalistic conventions by presenting the reportage as a transcription of real conversations and incorporating fictional elements, a practice known as "literary smuggling." It explores the tradition of journalist-writers in Latin American literature.